Qur’anic Ta‘lim and Early Childhood Character Formation in Raudhatul Athfal (Islamic Preschools) in Makassar, Indonesia - Ramlah Yusran; Muhammad Yusuf; Hasyim Haddade; Sadaruddin Sadaruddin (Madrasah Tsanawiyah DDI Cilellang, 2026)
This study aims to analyze the implementation of Qur’anic ta‘lim in Raudhatul Athfal (RA), examine its contribution to early childhood character formation, and identify the supporting and inhibiting factors affecting its implementation. This research employed a qualitative approach using a multiple-case study design conducted at three RA in Makassar affiliated with Nahdlatul Ulama, Muhammadiyah, and Wahdah Islamiyah. Data were collected through in-depth interviews, participant observation, and documentation involving principals and teachers. Data were analyzed through within-case and cross-case analysis. The findings reveal that Qur’anic ta‘lim has been implemented systematically through the integration of faith, worship, morality, and prophetic stories into daily learning activities. Despite differences in instructional strategies, all three RA share a common orientation toward internalizing Qur’anic values through habituation, teacher role modelling, and Islamic school culture. Qur’anic ta‘limcontributes to the development of religious, social, and moral character, including honesty, responsibility, empathy, discipline, and respect for others. Its implementation is supported by program consistency, integrated learning materials, exemplary teachers, and a conducive school environment. However, limited parental involvement, socio-emotional challenges among children, and the need for more inclusive educational approaches remain obstacles. This study highlights Qur’anic ta‘lim as a pedagogical mechanism for fostering holistic character development in early childhood education.